The Use of Indigenous Language to Promote Public Policy in Indonesia - Ida Bagus Rai Putra; Ida Ayu Putu Aridawati; Ni Putu N. Widarsini; I Wayan Teguh; Aditya Wardhani; I Gede Bagus Wisnu Bayu Temaja (Westscience Press, 2024)
This article aims at establishing hypothesis-based suggestions in promoting government public policy toward Indonesian using indigenous language. This research was conducted descriptively to describe the phenomena found. The data were also obtained from libraries and related sources. The results of the study indicate that the rapid development of the Bahasa Indonesia does not necessarily eliminate the role of regional languages. This is because regional languages still have a vital function. The existence of regional languages makes it easy for the government to convey their policies, especially for people who still use regional languages. Therefore, it is important to always preserve regional languages.